Law and Literature – the Danish Way on a Danish Crime Story. Issue 1 (2nd January 2017) - Simonsen, Karen-Margrethe; Tamm, Ditlev
Abstract: This article presents an introduction to the field of law and literature in Denmark and a legal and literary reading of one of the Western world's first crime stories, "The Pastor of Vejlbye, " written by the Danish writer Steen Steensen Blicher in 1829. This is a story based on a true case of a possible miscarriage of justice from the seventeenth century. The reading focuses on Blicher's story, the role of the judge, the nature of false confessions, the issue of the death penalty, and the whole narrative and diaristic setting that establishes a strong tension between the epic self-explanation of the pastor and the weak and hesitant diaristic prose of the judge.